Modification of amphiphilic block copolymers for responsive and biologically active surfactants in complex droplets. (March 2023) - Durkin, Tyler J.; Barua, Baishali; Savagatrup, Suchol
Abstract: Concerns regarding the speed and portability of sensing devices have spurred development of numerous novel platforms. Complex emulsions with responsive surfactants have emerged as a promising class of materials for the detection of various pathogens and environmental toxins. Herein, we report a study of the amphiphilic block copolymer surfactant (BCP), polystyrene- block -poly(acrylic acid), and its use as a functional surfactant. We observe that the composition and molecular weight of BCPs affect the interfacial properties, specifically, more amphiphilic BCPs lead to greater reductions in interfacial tension at the water/oil interface. We further demonstrate that conformational change of poly(acrylic acid) leads to changes in the interfacial tension reductions at these interfaces. Next, we present modification of BCPs with trypsin through carbodiimide mediated amidation to produce functional BCP-trypsin. The modified polymers retain their surfactant capabilities, as well as the functionality of the initial trypsin. Furthermore, we successfully demonstrate the use of the modified polymers within the active complex emulsion framework and the ability of the emulsion framework to turn "on" and "off" functionality through shielding of the active compounds. These responses to chemical changes in their surrounding environment illustrate the potential use of amphiphilic block copolymers as the key component of a complex emulsion systems for sensing device that is rapid, portable, and produces results in real-time. Graphical abstract: Image, graphical abstract